2020
DOI: 10.1159/000512506
|View full text |Cite
|
Sign up to set email alerts
|

<b><i>Helicobacter pylori</i></b> Eradication Rates in Slovenia in the Period from 2017 to 2019: Data from the European Registry on <b><i>H. pylori</i></b> Management

Abstract: Background. Helicobacter pylori (H pylori) is the most common chronic bacterial infection in the world, affecting over 50% of the world’s population. H pylori is a grade I carcinogen, responsible for the development of 89% of non-cardia gastric cancers. In the present study, we analyzed the data for H pylori eradication treatments in Slovenia after the 3rd National recommendations were implemented. Patients and methods. Slovenia is part of the European Registry on H pylori Management (Hp-EuReg) since the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…A Slovenian study from the years 2013–2015 has concluded that even though only 11.4% of the total 1519 cases were lost to follow-up, the mITT eradication success rates were also suboptimal: the overall treatment effectiveness of standard triple therapy was only 72% and of the main second-line PPI, amoxicillin and levofloxacin regimen was 87.1% [ 45 ]. However, a more recent Slovenian study from the years 2017–2019 has clearly shown improvements: the 14 days duration first-line standard triple therapy has achieved optimal 93% success rate and the effectiveness of the main second-line 14 days regimen was 89% [ 46 ]. The already mentioned data from 21,533 cases from Hp-EuReg has shown significantly increasing H. pylori eradication rates in Eastern Europe (from ~62% to more than 80%) and eradication rates ranging from ~80% to >90% in other parts of the Europe [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…A Slovenian study from the years 2013–2015 has concluded that even though only 11.4% of the total 1519 cases were lost to follow-up, the mITT eradication success rates were also suboptimal: the overall treatment effectiveness of standard triple therapy was only 72% and of the main second-line PPI, amoxicillin and levofloxacin regimen was 87.1% [ 45 ]. However, a more recent Slovenian study from the years 2017–2019 has clearly shown improvements: the 14 days duration first-line standard triple therapy has achieved optimal 93% success rate and the effectiveness of the main second-line 14 days regimen was 89% [ 46 ]. The already mentioned data from 21,533 cases from Hp-EuReg has shown significantly increasing H. pylori eradication rates in Eastern Europe (from ~62% to more than 80%) and eradication rates ranging from ~80% to >90% in other parts of the Europe [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have explored the efficacy and safety of PPI-Clarithromycin-Metronidazole for patients with penicillin allergy [ 24 , 25 , 28 , 30 , 32 , 35 , 39 , 41 ]. These studies utilized different PPIs, such as omeprazole, lansoprazole, esomeprazole, and rabeprazole, and the dose of metronidazole ranged from 500 mg to 1600 mg daily.…”
Section: Evidence For the Treatment Of H Pylori In...mentioning
confidence: 99%
“…• Previous failed therapy included: standard clarithromycin triple therapy (131 patients), sequential (32) and concomitant (37).…”
Section: European Global Datamentioning
confidence: 99%
“…In total, 200 patients from Spain and Italy were evaluated: previous failed therapy included standard clarithromycin triple therapy (131 patients), sequential (32), and concomitant (37). Compliance was reported in 96% of patients.…”
Section: European Registry On Helicobacter Pylori Management: Single-...mentioning
confidence: 99%
See 1 more Smart Citation